A fluorescent antibody test in the diagnosis of farmer's lung. Issue 10 (October 1972) - Parratt, D.; Peel, J. A.
Abstract : A test for farmer's lung is described employing the indirect fluorescent antibody technique. The test compared very favourably with standard precipitin tests, detecting 88% of a series of positive cases, as opposed to 38% detected by a precipitin test. The fluorescent antibody test, in addition, introduced some measure of quantitation of the serological response in the disease.